Pengaruh Debt To Equity Ratio (DER) dan Debt To Asset Ratio (DAR) Terhadap Return On Asset (ROA) pada PT. Mayora Indah Tbk - Eka Nur Faujia; Nafisah Nurulrahmatia (Inisiatif: Jurnal Ekonomi, Akuntansi dan Manajemen, 2024)
This research aims to determine the influence of the Debt To Equity Ratio and Debt To Asset Ratio (DAR) variables on Return On Assets (ROA) at PT. Mayora Indah Tbk. The population used in this research is all financial reports at PT. Mayora Indah Tbk has been listed on the Indonesian stock exchange since 1990, totaling 32 years for the period 1990-2022. The sample selection used a purposive sampling method based on certain criteria that were adjusted to the objectives of the research problem. The number of samples in this research was financial reports for 10 years at PT. Mayora Indah Tbk for the 2013-2022 period. The data analysis technique used in this research is Multiple Linear Regression Analysis using the SPSS version 26 program tool. The results of this research show that the Debt to Equity Ratio (DER) does not have a partially significant influence on Return On Assets (ROA) at PT Mayora Indah Tbk . Debt to Asset Ratio (DAR) does not have a partially significant influence on Return On Assets (ROA) at PT Mayora Indah Tbk.